2009
DOI: 10.1593/neo.81006
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of p53-Snail Binding, Promoted by Oncogenic K-Ras, Recovers p53 Expression and function

Abstract: Differentially from other kinds of Ras, oncogenic K-Ras, which is mutated approximately 30% of human cancer, does not induce apoptosis and senescence. Here, we provide the evidence that oncogenic K-Ras abrogates p53 function and expression through induction of Ataxia telangiectasia-mutated and Rad3-related mediated Snail stabilization. Snail directly binds to DNA binding domain of p53 and diminishes the tumor-suppressive function of p53. Thus, elimination of Snail through si-RNA can induce p53 in K-Ras-mutated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
86
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 34 publications
11
86
0
2
Order By: Relevance
“…Direct interaction of Snail and p53 reduces the expression of both proteins, whereas the inhibitor of their binding can induce p53 expression in K-Ras-mutated cells (Lee et al, 2009). We have also found that elimination of Snail can induce p53 in K-Ras-mutated cancer cells, but not in wild-type cancer cells.…”
Section: Introductionsupporting
confidence: 54%
See 4 more Smart Citations
“…Direct interaction of Snail and p53 reduces the expression of both proteins, whereas the inhibitor of their binding can induce p53 expression in K-Ras-mutated cells (Lee et al, 2009). We have also found that elimination of Snail can induce p53 in K-Ras-mutated cancer cells, but not in wild-type cancer cells.…”
Section: Introductionsupporting
confidence: 54%
“…p53 was induced more dominantly by si-Snal than by si-MDM2 in K-Rasmutated cell lines (Figure 1c; Bres et al, 2003), suggesting that Snail-mediated p53 suppression is not linked to MDM2-mediated p53 degradation. Indeed, we have already shown that Snail has not altered the p53 half-life, transcript or ubiquitin conjugation (Supplementary Figure S1a; Lee et al, 2009). To confirm this, we measured the p53 expression in Snail-transfected cells after treatment with ALLN/MG132.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations